The bivalve-bearing carbonate platform on the east Tethys during the middle Eocene and its response to the Tethys transgression - Fang, Shaobo; Xi, Dangpeng; Sun, Qi; Li, Dalei; Yang, Zhangzhang; Liu, Dan; Wu, Yuyang; Jiang, Tian; Wan, Xiaoqiao (Frontiers in Earth Science, 2024)
The Eocene was a typical greenhouse climate period in the history of the Earth, with high global sea level and extensive carbonate deposits developed in Tethys. During Eocene, carbonate platform deposits in the western Tarim Basin that belongs to the easternmost Tethys. However, the details of this carbonate platform and its complication for the paleoecology and paleoclimate is still unclear. This research focuses on the bivalve-bearing carbonates of the Kalataer Formation in western Tarim Basin, and detailed analyses of microfacies, biostratigraphy, paleoecology, as well as sea-level change was carried out. The bivalve of the Kalataer Formation is dominated by the Ostrea (Turkostrea) strictiplicata, Ostrea (Turkostrea) cizancourti, Ostrea (Turkostrea) strictiplicata, Ostrea (Turkostrea) strictiplicata and Sokolowia buhsii, and the age is middle Lutetian of the Eocene. The biota of the Kalataer Formation mainly lives in open shallow sea environments, with medium to low energy and rich nutrients and oxygen, representing a typical shallow marine ecosystem of carbonate platform. Microfacies and paleoecology indicates a large marine transgression event occurred in the western Tarim Basin during middle Eocene.